Comic Strips As The Media To Build Writing Skill Of Junior High School Students - Puput Zuli Ekorini (STKIP PGRI Nganjuk, 2018)
This article reports the results of a research dealing with: (1) the students’ writing skill which is taught using picture series, (2) the students’ writing skill which is taught using comic strips, (3) whether comic strips is more effective than picture series in teaching writing to the seventh grade students of a state islamic junior high school in Nganjuk. The research method was experimental method. The subjects of the research were the seventh grade students. There were two classes taken in this research, one as the experimental class and the another one as the control class. Each class consisted of 30 students. The experimental class was taught using comic strips and the control class was taught using picture series. The data were obtained by conducting a test after providing eigth meetings as the treatment for each class. The researcher analyzed the data using t-test to find whether comic strips was more effective than picture series in teaching writing. Based on the data analysis, the research findings are: (1) the students who were taught using picture series had low writing skill, (2) the students who were taught using comic strips had good writing skill, (3) the comic strips is more effective than picture series to teach writing for the seventh grade students of junior high school. It was showed from the computation of the t-test analysis at the significant level of 5% (sig = 0.05). The calculation showed that t value of 5.825 with the significant level of less than 0.05 is 0.000.